2011
DOI: 10.1002/malq.200910120
|View full text |Cite
|
Sign up to set email alerts
|

Existence of partial transposition means representability in cylindric algebras

Abstract: We show that the representability of cylindric algebras by relativized set algebras depends on the scope of the operation transposition which can be defined on the algebra. The existence of "partial transposition" assures this kind of representability of the cylindric algebra (while the existence of transposition assures polyadic representation). Further we characterize those cylindric algebras in which the operator transposition can be introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Further, the MGR axioms will be postulated. In [10] it is proven that the MGR axioms mean the existence of an operator "weak transposition" (or "partial transposition"). So by Resek-Thompson theorem (see (2.9)), the existence of such an operator yields representability by relativized set algebras.…”
Section: Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the MGR axioms will be postulated. In [10] it is proven that the MGR axioms mean the existence of an operator "weak transposition" (or "partial transposition"). So by Resek-Thompson theorem (see (2.9)), the existence of such an operator yields representability by relativized set algebras.…”
Section: Conceptsmentioning
confidence: 99%
“…where α ≥ 4 (see [9] As regards the representation theory of cylindric-like or polyadic-like algebras by relativized set algebras, see e.g., the references [2], [3], [4], [8], [9], [10], [13]. The references [1], [5], [6], [7], [12], [14], [15], [16] are related indirectly to the topic or are related to the applications.…”
Section: Polyadic-like Abstract Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used in Andréka and Thompson's proof is detailed in [12]. The r-representation of polyadic equality algebras by relativized set algebras was investigated in [6], [7] and [1]. In [6] it is shown that the background of the merry-go-round property is an axiom of transposition algebras (and it is also a property of polyadic algebras) and Resek and Thompson's theorem is closely related to transposition algebras.…”
mentioning
confidence: 99%
“…The r-representation of polyadic equality algebras by relativized set algebras was investigated in [6], [7] and [1]. In [6] it is shown that the background of the merry-go-round property is an axiom of transposition algebras (and it is also a property of polyadic algebras) and Resek and Thompson's theorem is closely related to transposition algebras. The direct predecessor of the research here is the investigation of the representability of transposition algebras in [7].…”
mentioning
confidence: 99%